Micro-mechanical behavior of a single grain with atomic-level variations in composition via additive manufacturing - Xin Wang; Jacob Norman; Baolong Zheng; Benjamin MacDonald; Enrique J. Lavernia; Julie M. Schoenung (Materials Research Letters)
Additive manufacturing offers precise control over part geometry and material composition, making it ideal for creating functionally integrated materials (FIMs). A Ni-Al FIM was fabricated using directed energy deposition (DED) to investigate how local composition variations affect microstructure, precipitation, and mechanical behavior. Advanced microscopy characterization revealed a novel grain structure with distinct compositional regions and a composition transition interface. These distinct regions within a single grain led to abrupt changes in the deformation response, as demonstrated through in-situ micropillar compression. These findings underscore the potential of additive manufacturing to engineer material behavior at the microscale, advancing materials design and manufacturing.